Enhancing Transjakarta Bus Service Quality: An Educational Perspective on Urban Development and Traffic Mitigation Using QFD Method - Firdaus, Hendy Yusman; Andraiko, Heru; Isradi, Muhammad; Sudrajat, Kukuh Mahi (Journal of Educational Management Research, 2025)
This study aimed to identify ways to enhance service quality, with the expectation of providing effective handling solutions and input for related parties in the context of sustainable urban development, particularly in Transjakarta. One hundred surveys were sent to passengers utilizing Transjakarta services on the BKN-Depok route, after which the data were processed and analyzed using IPA and QFD methodologies. Based on the results of the analysis of the Importance Performance Analysis (IPA) and Quality Function Deployment (QFD) methods, here is a positive relationship between fulfillment of customer requirements identified through QFD and improved bus performance, strengthening service maintenance and repair SOPs and periodic monitoring and evaluation of the system are the main concerns and must be improved. This study provides valuable insights for educational management, particularly in developing curricula that integrate aspects of public services and urban transportation. The findings underscore the importance of enhancing students’ understanding of quality management methodologies, such as IPA and QFD, to improve the management of sustainable public transportation systems.